Utilization of cocopro1 in dried ice cream mix by vacuum drying - Saulog, Susan S.
The study aimed to utilize cocopro ^1 ( spray dried coconut skim milk) in dried ice cream mix, by partial substitution for cow's skim milk. This involved the determination of a recommended percent composition of the dried ice cream mix which resulted as follows: 30.9% butterfat, 27% cocopro^1 - NFMS (non-fat-milk-solids) in one to one proportion, 40% sugar and 1.5% carboxymethyl-cellulose (CMC) with 0.6% final moisture content. Drying of the mix for 15 minutes at 65°C produced a final moisture content of 0.6%. The storage temperature of 15°C (refrigeration temperature) for this product was found to delay fat rancidity.